No Time Dependence of Ciprofloxacin Pharmacokinetics in Critically Ill Adults: Comparison of Individual and Population Analyses - Šíma, Martin; Michaličková, Danica; Ryšánek, Pavel; Cihlářová, Petra; Kuchař, Martin; Lžičařová, Daniela; Beroušek, Jan; Hartinger, Jan Miroslav; Vymazal, Tomáš; Slanař, Ondřej (Pharmaceutics, 2021)
The aim of this prospective PK study was to evaluate the pharmacokinetics of ciprofloxacin dosed within the first 36 h (early phase) and after 3 days of treatment (delayed phase) using individual and population PK analysis. The secondary aim of the study was to evaluate possible dosing implications of the observed PK differences between early and delayed phases to achieve a PK/PD target for ciprofloxacin of AUC24/MIC ≥ 125. Blood concentrations of ciprofloxacin (1 and 4 h after dose and trough) were monitored in critically ill adults in the early and delayed phases of the treatment. Individual and population PK analyses were performed. Complete concentration-time profiles in the early phase, delayed phase, and both phases were obtained from 29, 15, and 14 patients, respectively. No systematic changes in ciprofloxacin PK parameters between the early and delayed phases were observed, although variability was higher at the early phase. Both individual and population analyses provided similar results. Simulations showed that after standard dosing, it is practically impossible to reach the recommended ciprofloxacin PK/PD target (AUC/MIC ≥ 125) for pathogens with MIC ≥ 0.5 mg/L. A dosing nomogram utilizing patients' creatinine clearance and MIC values was constructed. Both individual and population analyses provided similar results. Therapeutic drug monitoring should be implemented to safeguard the optimal ciprofloxacin exposure.
Keywords: ciprofloxacin; renal function; NONMEM; pharmacokinetics; dosing; covariates